What Determines Financial Knowledgeamong Urban Indians? - Chauhan, Srishti (International Journal of Psychosocial Rehabilitation, 2020)
Financial literacy has been researched at depth in the past literature with a lot of emphasis on the successful outcomes reflected in positive savings, consumption and investment behavior. For a considerable time in the past, financial knowledge had proxied financial literacy and the dimension has received constant spotlight on issues like how, when and what type of financial knowledge individuals attain in a given socio- economic and demographic landscape. The present study is an attempt to closely understand the determinants of financial knowledge among the educated urban Indians working in the organized private sector, who are exposed to a multitude of complexities in terms of choice in the dynamic financial environment. As opposed to the majority of the literature, gender differences were not observed in our study. But, financial knowledge was higher among young, higher-income individuals, those with subject specialization in economics, finance or commerce and whose mother had a post-graduate degree. The study bridges the gap in the scarce literature in India and the findings have important implications for policymakers, financial education trainers, institutions rendering a closer look into financial literacy amidst the socio-cultural context.